Optical fiber refractometer based metal ion sensors - Tan, Rex Xiao (2020)
Research into optical fiber refractometers yielded remarkable results over the past decade. Numerous sensing schemes were proposed and demonstrated, which possessed different advantages while facing unique limitations. On top of their obvious applications in measuring refractive index changes of the ambient environment, several studies reported advanced applications of such sensors in heavy metal ion detection by means of surface coating of the refractometers with heavy metal ion sensitive materials. This paper surveys the effort these optical fiber metal ion sensors based on surface coated optical fiber refractometer, discusses different technologies and methods involved, and highlights recent notable advancements.